2014
DOI: 10.17348/era.12.0.551-560
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Assessment of Moringa oleifera Lam. in Southern Benin (West Africa)

Abstract: Research AbstractFor decades, plant species, particularly those used as non-tree forest products (NTFPs), have been known to play an important role in the livelihood of local populations, particularly in rural Africa. The present study investigated the uses of various parts of Moringa oleifera Lam. in southern Benin. It aimed at capturing indigenous knowledge on the uses of M. oleifera as a preliminary step toward future efforts to devise better management options of this plant species. An ethnobotanical surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 18 publications
(17 reference statements)
1
7
0
2
Order By: Relevance
“…Many of the plant use reports highlighted in this study overlap with those reported in ethnobotanical studies conducted in West Africa and Europe. M. oleifera (Moringa), which informants in this study reported to be useful for hypertension, cough, and diabetes, has been documented for the same traditional uses in both Benin and Ghana (Oppong Bekoe et al, 2020;Agoyi et al, 2014). Additional parallels are seen with A. indica (Neem), which is used for diabetes and anti-bacterial purposes both in Nigeria and in Barbados, as demonstrated by our findings (Lifongo et al, 2014).…”
Section: Discussionsupporting
confidence: 74%
“…Many of the plant use reports highlighted in this study overlap with those reported in ethnobotanical studies conducted in West Africa and Europe. M. oleifera (Moringa), which informants in this study reported to be useful for hypertension, cough, and diabetes, has been documented for the same traditional uses in both Benin and Ghana (Oppong Bekoe et al, 2020;Agoyi et al, 2014). Additional parallels are seen with A. indica (Neem), which is used for diabetes and anti-bacterial purposes both in Nigeria and in Barbados, as demonstrated by our findings (Lifongo et al, 2014).…”
Section: Discussionsupporting
confidence: 74%
“…These include: Aïzo (Atlantic Department); Fons (Littoral and Zou Departments); Idaasha, Ifè, Isha (Collines Department); Mahi (Zou and Collines Departments); Goun, Yoruba (Ouémé and Plateau Department); Adja (Mono and Couffo Departments). Some authors who have worked in the same geographical area found the inhabitants belonging to different socio-cultural groups [ 76 78 ]. This study therefore shows that Benin is home for a wide variety of medicinal plant species used in the treatment of candidiasis.…”
Section: Discussionmentioning
confidence: 99%
“…All parts of the species are traditionally used for different purposes, but leaves are generally the most used (Popoola and Obembe, 2013;Sivasankari et al, 2014). Seven use categories of M. oleifera, namely medicine, food, fodder, fencing, firewood, coagulant and gum have been identified (Popoola and Obembe, 2013;Agoyi et al, 2014;Sivasankari et al, 2014). The species is mostly used as a traditional medicine and food (Popoola and Obembe, 2013;Agoyi et al, 2014;Sivasankari et al, 2014).…”
Section: Significance Of Moringamentioning
confidence: 99%